2021
DOI: 10.30892/gtg.362spl12-694
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Younger Tourist’ Intention Toward Environmentally Responsible Behavior

Abstract: Despite the significant contribution of the tourist growth to the economics, besides the concern of its impact on the environment has gained much attention. This integrated green image in the theory of planned behavior to determine the factor influencing Younger tourist environmentally responsible intention behavior particularly recycling behavior intention. The study identified the factors influencing tourist environmentally responsible behavior within the lens of the theory Of Planned Behavior (TPB). The fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 5 publications
1
9
0
1
Order By: Relevance
“…Because the TPB has good predictive and explanatory capabilities in behavior research, it is widely used in various aspects, There have been many studies used the TPB model in the research area of environmental behaviors (Yuriev et al, 2020;Alzubaidi et al, 2021;Aziz et al, 2021;Fenitra et al, 2021;Han, 2021;Zhang et al, 2021;Zheng et al, 2022), green purchase (Emekci, 2019;Han, 2020;Liu et al, 2020), revisit behaviors (Manosuthi et al, 2020;Meng et al, 2020;Abbasi et al, 2021;Deng et al, 2021;Soliman, 2021), food delivery services (Troise et al, 2020;Choe et al, 2021), destination choose (Juschten et al, 2019b;Liu et al, 2021;Azhar et al, 2022;Mohamad et al, 2022Mohamad et al, ), 10.3389/ffgc.2022 digital currency (Radic et al, 2022) these studies have shown that ATT, SN, and PBC positively affected the behavioral intention. Accordingly, this research proposes the hypothesis as follows:…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Because the TPB has good predictive and explanatory capabilities in behavior research, it is widely used in various aspects, There have been many studies used the TPB model in the research area of environmental behaviors (Yuriev et al, 2020;Alzubaidi et al, 2021;Aziz et al, 2021;Fenitra et al, 2021;Han, 2021;Zhang et al, 2021;Zheng et al, 2022), green purchase (Emekci, 2019;Han, 2020;Liu et al, 2020), revisit behaviors (Manosuthi et al, 2020;Meng et al, 2020;Abbasi et al, 2021;Deng et al, 2021;Soliman, 2021), food delivery services (Troise et al, 2020;Choe et al, 2021), destination choose (Juschten et al, 2019b;Liu et al, 2021;Azhar et al, 2022;Mohamad et al, 2022Mohamad et al, ), 10.3389/ffgc.2022 digital currency (Radic et al, 2022) these studies have shown that ATT, SN, and PBC positively affected the behavioral intention. Accordingly, this research proposes the hypothesis as follows:…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…To achieve a more sustainable society, encouraging hikers to participate in a variety of PEB can subsequently increase favorable environmental outcomes and lessen the severity of global environmental challenges (Goh, 2020;Udall et al, 2020;Choi and Kim, 2021;Esfandiar et al, 2022). Previous studies about PEB have generally focused on personal factors regarding tourists, such as their attitude (ATT), subjective norm (SN), and perceived behavioral control (PBC) mechanisms as well as the environmental behavioral intention of theory of planned behavior (TPB) (De Leeuw et al, 2015;Han, 2020;Meng et al, 2020;Yuriev et al, 2020;Alzubaidi et al, 2021;Aziz et al, 2021;Fenitra et al, 2021;Panwanitdumrong and Chen, 2021;Singh and Kaur, 2021;Zhang et al, 2021;Loureiro et al, 2022;Zheng et al, 2022); awareness of consequences (AC), ascription of responsibility (AR), and personal norm (PN) of the norm activation theory (NAM) (Meng et al, 2020;Alzaidi and Iyanna, 2021;Bai and Zhang, 2021;O'Connor and Assaker, 2021;Han et al, 2021;Cao et al, 2022;Jeon et al, 2022;Kang, 2022;Long et al, 2022;Loureiro et al, 2022;Song et al, 2022;Zhang et al, 2022). However, there are many influencing factors of personal PEB, and there are complex interrelationships, there are both have direct and indirect effects (Han, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This research explored influential factors to provide a scientific basis for building a stronger environmental protection culture and increased ecological protection awareness. The existing studies on ERB place more attention on individual visitor characteristics [9][10][11]; however, external factors such as the situations experienced by visitors are less examined. Thus, the impacts of different external situation factors on visitor ERB were analyzed in this research.…”
Section: Introductionmentioning
confidence: 99%
“…The long-term socioeconomic and environmental health of a tourism destination depends on tourists' environmentally responsible behavior (TERB) [81][82][83], which is a key component of the destination management for sustainability [84,85]. It is frequently thought that environmentally responsible attitudes, knowledge, and behavior are all influenced by nature-based tourism [50,86].…”
Section: Tourists' Environmentally Responsible Behaviormentioning
confidence: 99%